Burdens of Proof in Medical Civil Liability Based on Doctrine and Case Law of the Supreme Court of Justice - Santos Ballesteros, Iván; Ortiz Arciniegas, Emma; Ruiz Alarcón, Ruth (DIXI, 2016)
Introduction: this article is the result of a research project with the same name conducted by the research group Legal Hermeneutics of the research line Legal Analysis in the School of Legal and Political Sciences at the Universidad Autónoma de Bucaramanga (unab), Colombia. Methodology: the research conducted is descriptive with documentary review techniques; the deductive method is used. Its general objective is to analyze the doctrine and case law evolution of the Civil Division of the Supreme Court of Justice in terms of burden of proof in medical liability proceedings for the period between 1990 and 2014. It is noteworthy that, regarding the demonstration of the de facto assumption of the rules containing the legal effct they pursue in medical liability proceedings, there is a question about whether the burden of proof belongs to the plaintif (static burden of proof) or to the party who is in the best condition to bring in evidence or clarify the facts of the dispute, whether plaintif or defendant (dynamic burden of proof). Results and conclusions: the answer to the said legal problem is given by the evolution of two pronouncements by the Supreme Court of Justice, referred to for their analysis as line founder (Judgment of March 5, 1940) and Archimedean (Judgement of November 14, 2014)